Membangun Keberhasilan : Studi Kelayakan Bisnis Peternakan Ayam Broiler KJ Farm Melalui Analisis Potensi Pasar dan Strategi Pemasaran - Mustaqfiroh, Novi Kholifatul; Affandy, Faza Ainunnisa; Ariba, Nadia (Maliki Interdisciplinary Journal, 2025)
This research analyzes the feasibility of KJ Farm’s broiler chicken farming business through market potential and marketing strategy analysis. The analysis was conducted using the STP (Segmenting, Targeting, Positioning) method to determine the target market, a competitive matrix analysis to determine KJ Farm’s position compared to competitors, and an analysis of supply and demand to assess market share. The results of the analysis show that KJ Farm has good market potential with a wide target market, a strong position, and opportunities to increase market share. However, KJ Farm needs to develop a more structured marketing program to reach its full potential. This study concludes that KJ Farm’s broiler chicken farming is viable in terms of market and marketing aspects, with the potential to grow faster with the implementation of appropriate marketing strategies.